PROBLEMS AND PROSPECTS OF DISTANCE EDUCATION IN UZBEKISTAN - Shermuhamedova, Nigina (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
Distance education as a form of education spoiled the beginning in the 20th century and gained wide popularity in the 21st century. It is characterized by continuity, flexibility, modularity, independence and provides access to education for all citizens, regardless of location, as well as people with disabilities. Distance education makes it possible to respond most adequately and flexibly to the needs of society, to provide wide access to education. In this regard, this article reveals the problems of virtual education and the prospects for its development.